ECONOMIC ANALYSIS OF BAGEA SAGU CAKE BUSINESS IN KENDARI CITY, SOUTHEAST SULAWESI - Asriani Asriani (Universitas Muhammadiyah Kendari, 2021)
Sago is a local food commodity in Southeast Sulawesi. Sago flour is the raw material for making Bagea cake a typical snack product of Kendari City. This study aims to determine the level of profit in the business of processing sago flour into Bagea cake products in the home industry in the city of Kendari . This research was conducted in June 2021. Bagea sago cake processing technology includes roasting sago flour, mixing sago flour ingredients, printing, heating in the oven, packaging, and marketing. The data collection method used was through recording through a questionnaire which was then analyzed. The analysis method used is cost analysis, revenue analysis, and profit analysis. Based on the results of the analysis, it is known that the total cost used is Rp. 1,170,000, total revenue of Rp. 3,000,000 and the total profit is Rp. 1,736,459. Thus, the Bagea cake processing business is economically profitable to develop.